(untitled) (Al-Mansour Journal, 2022)
The aim of human lower limb rehabilitation robot is to regain the ability of motion and to strengthen the weak muscles. This paper proposes the design and modelling of four Degree Of Freedom (4-DOF) lower limb wearable rehabilitation robot. This robot is located in, hip, knee and ankle joints to enable the patient for motion and turn in both directions. The joints are actuated by Pneumatic Muscles Actuators (PMAs). The PMAs have very great potential in medical applications because the similarity to biological muscles. This work proposes the structure of the robot to eliminate the singularity problem that exists in the inertia matrix. Also, the effects of disturbance on the robot joints and frictions in robot joints and in PMAs are taken into consideration. The designed robot can be used for the right side leg of an elderly persons whose ages beyond 40th years old. Since the 4-DOF rehabilitation robot actuated by PMAs has high nonlinearity. An intelligent position controller to control each joint position is designed and simulated using two schemes; Mamdani PD-like fuzzy logic and Takagi-Sugeno-Kang (TSK)-PD-like Fuzzy logic to improve the time response specifications such as minimum overshoot, minimization of oscillation and disturbance rejection to track the desired medical trajectory. A comparison between the two schemes shows an enhancement in the results of the second type as compared with the first one.